Penyusunan Laporan Keuangan berdasarkan Standar Akuntansi Keuangan Entitas tanpa Akuntanbilitas Publik pada Perusahaan Omah Jenang di Kabupaten Blitar - Meyta Zella Kurnia Indah (Jurnal Simki Economic, 2019)
One of the things that the Indonesian government really hopes for for its people in order to achieve their welfare in life is to be independent, independent, and not necessarily depend on what the government has given them but to be self-employed and not looking for work but to create jobs for themselves and other people. people around him, such as businesses in the field of services, transportation, culinary and others. Of course this will be formed through various types of businesses such as home industries, CVs, cooperatives or Small and Medium Enterprises (SMEs). The purpose of this study was to compare the quality of Omah Jenang's financial statements in Blitar with financial statements based on Accounting Standards for Micro, Small and Medium Entities. The research method used is quantitative descriptive research with a case approach. The results showed that in the process of implementing the existing accounting cycle, omah jenang company did not record transactions in the journal and journal entries to the general ledger in accordance with SAK ETAP and the accounting cycle in general. In the application of the preparation of financial statements made by the company in 2016-2018, it is not in accordance with SAK ETAP because it only makes the presentation of financial statements in the form of a balance sheet and income statement. Omah jenang company presents financial statements using simple accounting, namely by recognizing cash basis accounting. Measurements are made based on the nominal value of the accounts available in the financial statements of the omah jenang company and the existing disclosures are also not in accordance with SAK ETAP.